2015
DOI: 10.1007/s00213-015-4162-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic potential of Ayahuasca: acute intake increases mindfulness-related capacities

Abstract: The present findings support the claim that ayahuasca has therapeutic potential and suggest that this potential is due to an increase in mindfulness capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(179 citation statements)
references
References 54 publications
17
144
1
17
Order By: Relevance
“…Full-text reports of these citations were obtained for more detailed evaluation. Following detailed examination of the reports, all 27 citations were included (Alonso et al, 2015;Barbosa et al, 2005Barbosa et al, , 2009Bouso et al, 2012Bouso et al, , 2013Bouso et al, , 2015Da Silveira et al, 2005;De Araujo et al, 2012;Doering-Silveira et al, 2005a;Dos Santos et al, 2007, 2011, 2012Fábregas et al, 2010;Frecska et al, 2012;Grob et al, 1996;Halpern et al, 2008;Osório et al, 2015;Palhano-Fontes et al, 2015;Riba et al, 2001Riba et al, , 2002aRiba et al, , 2002bRiba et al, , 2003Riba et al, , 2004Riba et al, , 2006Sanches et al, 2016;Soler et al 2015;Thomas et al, 2013). Another reference was included after searching the bibliography of the selected citations (Schenberg et al, 2015).…”
Section: Study Selectionmentioning
confidence: 99%
“…Full-text reports of these citations were obtained for more detailed evaluation. Following detailed examination of the reports, all 27 citations were included (Alonso et al, 2015;Barbosa et al, 2005Barbosa et al, , 2009Bouso et al, 2012Bouso et al, , 2013Bouso et al, , 2015Da Silveira et al, 2005;De Araujo et al, 2012;Doering-Silveira et al, 2005a;Dos Santos et al, 2007, 2011, 2012Fábregas et al, 2010;Frecska et al, 2012;Grob et al, 1996;Halpern et al, 2008;Osório et al, 2015;Palhano-Fontes et al, 2015;Riba et al, 2001Riba et al, , 2002aRiba et al, , 2002bRiba et al, , 2003Riba et al, , 2004Riba et al, , 2006Sanches et al, 2016;Soler et al 2015;Thomas et al, 2013). Another reference was included after searching the bibliography of the selected citations (Schenberg et al, 2015).…”
Section: Study Selectionmentioning
confidence: 99%
“…Furthermore, ayahuasca has recently been reported to significantly increase mindfulness related capacities, reducing participants’ judgment and reactivity towards inner experiences, 24 hours after ayahuasca use in a sample of 25 healthy volunteers (Soler et al, 2015). Such effects may indicate a potential psychological mechanism mediating therapeutic effects of ayahuasca, as successful mindfulness-based treatments for depression have been shown to decrease brooding, in part by enhancing nonjudgmental awareness (Shahar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For future studies, we also suggest the use of zebrafish to test Ayahuasca exposure regimes on the development of drug seeking behavior. Studies have shown that regular ingestion of the brew is associated with a reduction in the consumption of abusive drugs (Fábregas et al, 2010; Thomas et al, 2013; Oliveira-lima et al, 2015; Soler et al, 2016), and this effect should be related to Ayahuasca action. Also, it would be important to invest in techniques that show changes in the brain (neurotransmitters, proteins, neuroplasticity) caused by Ayahuasca, in order to thoroughly understand the comparative effect of low vs. high and acute vs. chronic exposure of a drug that has been increasing used worldwide.…”
Section: Discussionmentioning
confidence: 99%